Effect of magnetic field on electromagnetic soliton evolution by different pulses - Aparna Sharma; Hitendra K. Malik; Harish Kumar; Sanjeev Goyal (Journal of Theoretical and Applied Physics)
Abstract Solitons evolve in a nonlinear and dispersive medium whenever the balance is obtained between the effects of dispersion and nonlinearity. In this work, we study the impact of an external magnetic field on electromagnetic soliton profile in nonrelativistic two-fluid plasma using IMEX scheme. We found that different kinds of perturbing pulses create two solitons of same characteristics, propagating in opposite directions. For the present study, we considered three kinds of perturbing pulses of equal amplitudes but different widths as 0.003, 0.011 and 0.015. The propagation characteristics of the solitons, viz. crest of soliton amplitude, its width and velocity, are evaluated under the impact of an external magnetic field. In addition, we generalize the case by examining different plasma models by selecting different mass and temperature ratios of the ions and the electrons. This is done at the fixed external magnetic field strength of 0.06T and 0.01 T.